(untitled) (Latakia University Journal -Biological Sciences Series, 2022)
A field experiment was conducted in Kadmous area in the 2020 agriculture season to study the response of of local tobacco variety (Shik Al-Benet) to increasing levels of N fertilization (0- 7- 14 and 21 kg N/Donom-1). Potassium humate was also added either no application (H0), foliar application (2 g/L-1), or applied to the soil before transplanting (HS= 1 kg.D-1). The experiment consisted of 12 treatments with 3 replicates. Plots were completely randomized in the experiment area. The analysis of variance showed a significant increase in all morphological parameters of tobacco leaves (leaves number, leaf length, leaf area, and leaf area for plant) with increasing rate of nitrogen fertilization. Humate application to the soil with low N rates increased leaves number, leaf length and total leaf area, which however, decreased by about 18 and 23% when humate was add along with higher N rates (N14 and N21) compared to treatment not receiving humate application. The dry weights of tobacco leaves increased right from the first rate of N application (7 kg N.D-1), and continued to increase gradually with increased N rates to reach 289.6 kg.D-1 at N21 with foliar application of humate. The soil dressing of humate increased significantly dry weight of tobacco leaves when N was not applied (177.8 kg.D-1). This constitute 30 and 31% increase compared to treatment didn’t receive any humate application in either types. Nitrogen application was the limiting factor to increasing concentrations and uptake of both nitrogen and potassium, which increase significantly with increasing N application irrespective of humate application. When humate was applied to the soil with no N, mineral content of N and K in the shoots were increased 36-44% compared treatment receiving foliar humate application or those not receiving any humate application.